2022
DOI: 10.3390/ijms23137097
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Renal Medullary Carcinoma

Abstract: Renal medullary carcinoma (RMC) is a rare renal malignancy that has been associated with sickle hemoglobinopathies. RMC is aggressive, difficult to treat, and occurs primarily in adolescents and young adults of African ancestry. This cancer is driven by the loss of SMARCB1, a tumor suppressor seen in a number of primarily rare childhood cancers (e.g., rhabdoid tumor of the kidney and atypical teratoid rhabdoid tumor). Treatment options remain limited due in part to the limited knowledge of RMC biology. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…Despite advancements in the understanding of this disease, no significant improvement in disease-specific survival has been observed over the past decade, and treatment is currently based on chemotherapy and nephrectomy, despite a lack of solid scientific evidence ( 18 20 ). In 2016, Beckermann et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advancements in the understanding of this disease, no significant improvement in disease-specific survival has been observed over the past decade, and treatment is currently based on chemotherapy and nephrectomy, despite a lack of solid scientific evidence ( 18 20 ). In 2016, Beckermann et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is often found at an advanced stage or with distant metastases, and recent studies have shown that SMARCB1 -deficient RMC is also associated with the sickle-cell trait [ 82 ]. Specific symptoms are usually abdominal pain, hematuria, and weight loss [ 80 ], while distant metastases can be found in the renal lymph nodes, adrenal glands, lungs, and liver [ 83 ]. Due to the prevalence of SMARCB1 -deficient RMC in children and adolescents and the aggressive nature of the tumor, early recognition and diagnosis are a priority for physicians.…”
Section: Smarcb1 -Deficient Renal Medullary Carcinomamentioning
confidence: 99%
“…With the advancement of detection technology in recent years, some characteristic manifestations of SMARCB1 -deficient RMC have been gradually proposed. First, in addition to the previously mentioned clinical symptoms and prodromal nature during adolescence, SMARCB1 -deficient RMC usually develops with SCT and SCD [ 83 ]. Secondly, the tumor is often already at a high grade at the time of detection, showing infiltrative growth and exhibiting a sieve or reticular appearance [ 85 , 86 ].…”
Section: Smarcb1 -Deficient Renal Medullary Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicated that RMC tumors often harbor translocations and deletions of tumor suppressor SWI/SNF-related matrixassociated actin-dependent regulator of chromatin subfamily B member 1 (SMARCB1) or rearrangement in anaplastic lymphoma kinase (ALK) [67]. The absence of SMARCB1 protein in RMC leads to activation of the c-MYC pathway and subsequently induction of high levels of DNA replication stress, which results in the upregulation of cell-cycle checkpoint pathways [68]. The presence of a BCR/ABL rearrangement was reported in one study.…”
Section: Renal Medullary Cell Carcinoma (Rmc)mentioning
confidence: 99%